Pemanfaatan Media Sosial Instagram Untuk Digital Branding Sebagai Strategi Pemasaran Produk Usaha Mikro - Kiki Nurtia Sibolga Marbun; Wirya Wardaya; Halimatus Sakdiyah; Muchamad Toha Yudo Pratama; Taufiq Ismail (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Media social has been widely used as one of the effective digital marketing methods in marketing products through digital marketing. This is due to its simple use and great impact on increasing sales and profits for microenterprises. One of the top-list social media to be used as a digital marketing tool is Instagram. In Bulak Banteng and Kedung Cowek villages, micro-entrepreneurs are yet not using Instagram as a promotional tool. The reason is that they lack the understanding and skills to maximize Instagram as a promotion tool for their products. Hence, it leads to a lack of competitiveness of their goods or services products in the market. Therefore, counseling and discussion activities were held as a form of the initial analysis of the obstacles faced by micro-entrepreneurs. Through training and assistance, the micro-entrepreneurs were expected to be able to increase their knowledge about the importance of using Instagram as a product promotion tool. Then, monitoring and evaluation were conducted to analyze the changes after training and mentoring activities. The results of these activities reveal a change that micro-entrepreneurs realize that the use of Instagram as a marketing tool is able to provide some benefits, such as a marketing strategy without exceeding costs as well as an increasingly broad target market. Micro-entrepreneurs started to build their digital marketing links and began to actively use Instagram as a product promotion tool.